Efektivitas Worksite Health and Wellness Programs dalam Memperbaiki Komposisi Tubuh, Kebugaran, dan Faktor Risiko Kardiometabolik: The Effectiveness of Worksite Health and Wellness Programs in Improving Body Composition, Fitness, and Cardiometabolic Risk Factors in Employees - Kurdanti, Weni; Astuti, Rini Wuri; Widyawati, Herni Endah Endah (Amerta Nutrition, 2026)
Background: Non-Communicable diseases (NCDs) are increasing among Indonesia’s productive and pre-elderly populations. Cardiometabolic risk factors such as obesity, dyslipidemia, hypertension, and hyperglycemia substantially contribute to this burden, accounting for approximately 70-75% of all deaths. The workplace offers a strategic location for promotional and preventive interventions through Worksite Health and Wellness Programs (WHWPs). Objectives: To assess the effectiveness of WHWPs in improving body composition, fitness, and cardiometabolic risk factors among employees. Methods: A quasi-experimental design with a one-group pre–post test was applied to 35 employees aged 30–60 years with BMI ≥25 kg/m². The 12-week intervention included nutrition education and combined cardio and strength training. The variables measured included anthropometry, body composition, fitness, blood pressure, blood glucose, total cholesterol, dietary intake, and nutritional knowledge. Data were analyzed using paired t-tests, repeated measures ANOVA, and Friedman’s test. Results: Significant improvements were observed in body composition, with reductions in body fat percentage (from 32.81 to 31.46%; p-value=0.005), subcutaneous fat (from 28.67 to 26.84; p-value=0.042), and an increase in skeletal muscle mass (from 25.70 to 26.45; p-value=0.015). Fitness improved significantly (from 32.39 to 35.80; p-value<0.001). Total cholesterol decreased (from 199.94 to 177.40 mg/dL; p-value=0.003), while blood glucose and blood pressure did not change significantly. Natrium intake decreased (from 3209 to 1740 mg; p-value=0.013) and nutrition knowledge scores increased (from 51.65 to 57.33; p-value=0.006). Conclusions: WHWPs effectively improved body composition and fitness and reduced cardiometabolic risk factors among employees.